Pengaruh Praktik Total Quality Management (TQM) terhadap Budaya Kualitas, Daya Saing dan Kinerja Perusahaan (Studi pada Industri Manufaktur di Kota Makassar) - Munizu, Musran; .., Surachman; sallim, ubud; .., Solimun (Jurnal Aplikasi Manajemen, 2012)
The purpose of this research is to investigate the TQM practices effect on quality culture, competitiveness, and firm performance both directly and indirectly at Manufacturing Industry in Makassar. Company as unit of analysis in this research. There are 114 companies as sample, where company manager as respondent. Method of Analysis used in testing hypothesis is Structural Equation Modeling (SEM). Then, qualitative information used to find the addition explanation to support the result of hypothesis examination. The results shows that TQM practices have significant effect on quality culture, competitiveness, and company performance directly. Quality culture has significant effect on competitiveness directly. Competitiveness has direct effect on firm performance. Quality culture hasn't significant effect on firm performance directly, but quality culture can be able to improve the firm performance by competitiveness. TQM practices can be able to improve the firm performance by competitiveness. While, the indirect effect of TQM practices on firm performance by quality culture aren't significant.